Implementasi Materi Kisah Nabi pada Mata Pelajaran Pendidikan Agama Islam Menggunakan Media Audio Visual di Kelas IV Sdn 008 Tambusai Utara Riau - Dewi Rafi Martini; Romelah romelah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this study was to describe the learning objectives of Islamic Religious Education on the material of the story of the Prophet using audio-visual media in class IV SDN 008 Tambusai Utara Riau and its implementation and results. This research approach uses qualitative research with a case study type, carried out at SDN 008 Tambusai Utara, Jalan Pelajar Simpang Genjer, Tanjung Medan Village, North Tambusai District, Riau. Informants in this study were PAI teachers and 9 fourth grade students. While the data collection techniques by observation, interviews, and documentation. In this study using data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results showed that the first, the teacher's goal in using audio-visual media for the story of the Prophet in the subject of Islamic Religious Education in class IV SDN 008 Tambusai Utara Riau is to increase students' understanding of the subject of Islamic Religious Education. Therefore, with the existence of audio-visual media, the teacher hopes that it can encourage students' learning motivation, clarify and simplify the material in a simple way, and will be easy to understand. Second, the process of implementing the Prophet's story material on the subject of Islamic Religious Education using audio-visual media in grade IV SDN 008 Tambusai Utara Riau. the story of the Prophet, speakers, and worksheets. Third, the results of the implementation of the Prophet's story material in the subject of Islamic Religious Education using audio-visual media in class IV SDN 008 Tambusai Utara Riau, which has 9 students consisting of six boys and three girls, on average, fourth grade students get the results. learning well by obtaining a score frequency of 75-80 compared to before the teacher implemented audio-visual media as a learning tool for Islamic Religious Education, which scored below the KKM with a score frequency of 60-65.